2006
DOI: 10.1038/sj.ejcn.1602442
|View full text |Cite
|
Sign up to set email alerts
|

Relations between obesity and hypertension: preliminary data from a cross-sectional study in primary schoolchildren: The children study

Abstract: Objective: To record the prevalence of overweight, obesity and hypertension in primary schoolchildren living in one of the poorest regions in Europe and furthermore to identify certain behavioural, lifestyle and physiological parameters associated with body mass index (BMI) and blood pressure (BP). Design: Cross-sectional study. Setting: Nineteen primary schools within the county of Ioannina, Greece. Subjects and methods: Demographic, dietary and physical activity data as well as anthropometrical, BP and cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
19
1
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 48 publications
(47 reference statements)
9
19
1
8
Order By: Relevance
“…[5][6][7] There are only few data about the prevalence of hypertension in children and adolescents, mainly in studies with restricted sample size, whereas information about the variables that influence BP is limited. [8][9][10] However, the available evidence suggests that the prevalence of hypertension in Greek children exceeds the rates reported for respective age groups in other countries. [8][9][10] This study was designed to assess the prevalence of high BP in adolescents and its potential change in recent years, as well as to investigate associated dietary and lifestyle factors.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…[5][6][7] There are only few data about the prevalence of hypertension in children and adolescents, mainly in studies with restricted sample size, whereas information about the variables that influence BP is limited. [8][9][10] However, the available evidence suggests that the prevalence of hypertension in Greek children exceeds the rates reported for respective age groups in other countries. [8][9][10] This study was designed to assess the prevalence of high BP in adolescents and its potential change in recent years, as well as to investigate associated dietary and lifestyle factors.…”
Section: Introductionmentioning
confidence: 71%
“…[8][9][10] Angelopoulos et al 9 reported that the prevalence of systolic and diastolic hypertension was 28.1 and 7.8% for boys and 26.4 and 17% for girls in schools of Northern Greece. Similarly, in another Greek study, 39.3 and 32.3% of boys presented with systolic and diastolic BP above normal, respectively, whereas for girls, the respective proportions were 36.3 and 36.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, there are only a few data regarding which is the best available marker of obesity in relation to BP. [17][18][19][20][21] Finally, office blood pressure (OBP) that is classically used for the evaluation of hypertension in children and adolescents may lead to misinterpretation of the true BP. 22 Recently, it has been shown that home blood pressure (HBP) monitoring is an applicable and more reliable method for the evaluation of BP in children.…”
Section: Introductionmentioning
confidence: 99%
“…Children's 'poor' diet observed in developed countries during last decades have resulted in an increasing prevalence of risk factors for chronic diseases such as obesity, high blood pressure and increased cholesterol levels in children (Hampl et al, 1999;Devaney et al, 2004;Kranz et al, 2004;Muntner et al, 2004;Angelopoulos et al, 2006;Magkos et al, 2006;Manios et al, 2008). Both the aforementioned clinical risk factors and several behavioral factors, such as unhealthy dietary habits or lifestyle patterns, originating in early life seem to track into adulthood increasing the risk for developing chronic diseases in adult life (Boulton et al, 1995;Hesketh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%